The efficacy of transgingival probing in class II buccal furcation defects treated by guided tissue regeneration - Monika Bansal; Tej Bali Singh (Wolters Kluwer Medknow Publications, 2016)
Background: The objectives of the present study were to establish transgingival probing as an evaluating method in the clinical studies of periodontal regenerative techniques and to compare the effectiveness of transgingival probing to the surgical entry. Materials and Methods: Ten systemically healthy persons (20-50 years) with moderate to severe chronic periodontitis participated in this study. These cases were recruited into the study only when they fulfilled the eligibility criteria. Vertical probing depth (VPD) and horizontal probing depth (HPD) of furcation defects were measured with and without opening the flap, following local anesthesia during initial surgery and at 6 months after collagen membrane placement. The defect fill (DF) was also noted. The mean measurements of clinical parameters were compared by two-tailed paired t-test at 5% level of significance. Results: The difference between the measurements of VPD and HPD taken during transgingival probing and after opening the flap was lie in the range of 0.10-0.30 mm at the time of initial surgery and 6 months after surgery that was not statistically significant. Persons experienced slight discomfort or pain during opening the flap as compared to transgingival probing, and this method was also appreciated by the patients as it is easy, simple and does not involve the surgical procedure. Conclusion: The results of the study suggest that measurements recorded during transgingival probing and after opening the flap do not influence the required outcome of regenerative therapies, i.e., DF that was not statistically significant difference from surgical reentry. Therefore, it was concluded that transgingival probing could be used as evaluating parameters to see the outcome of regenerative surgeries and the surgical reentry procedure may be avoided because it is a second surgical procedure, time-consuming and interrupts the healing process.